A SEMIOTIC ANALYSIS OF SASIRANGAN BATIK MOTIFS DELIVERING LOCAL WISDOM OF TANAH LAUT REGENCY - Decky C. Kananto Lihu; Muzahid Akbar Hayat; Lasmiati (RADJA PUBLIKA, 2025)
Wisdom is interpreted in the local culture of Sasirangan cloth, one of its products is the Kijang and Jagung motif which is seen as increasingly important in supporting economic welfare and also as a process of creation, creativity, ideas, and concepts from a person or group that can produce Sasirangan works or products. The use of local wisdom culture makes creative economies utilize creativity, individual creativity, and individual skills and talents to create welfare and employment. The purpose of this study is 1). To analyze the connotation of the sasirangan batik motif that depicts the local wisdom of Tanah Laut Regency. 2) To analyze the denotation of the sasirangan batik motif that depicts the local wisdom of Tanah Laut Regency. 3) To analyze the meaning built on the sasirangan batik motif that depicts the local wisdom of Tanah Laut Regency. The type of research used is qualitative, namely in the initial stage the researcher conducts exploration, then data collection is carried out in depth, starting from observation to compiling reports. Data collection techniques use observation, interview and documentation methods. The results of the study show that 1) The connotation of the sasirangan batik motif depicts a spirit with agility and wisdom and deer have an agile nature, it is expected that users of sasirangan cloth with deer motifs can apply these characteristics. 2) The denotation of the sasirangan batik motif that depicts the local wisdom of Tanah Laut Regency is interpreted as a symbol of agility, adaptability, and the ability to face challenges. 3) The sasirangan batik motif contains a philosophy of life that teaches how to live a good life, be useful to others, and maintain a balance between the world and the hereafter. The sasirangan batik motif can also be a symbol of Tanah Laut Regency which reflects the identity of local wisdom, culture and traditions typical of Tanah Laut.